DEBIROKRATISASI PELAYANAN: “ANALISIS PELAYANAN RETRIBUSI PARKIR DI PAMEKASAN” - Anam, Syaiful (Universitas Madura, 2017)
The paradigm of public administration to putting public services of the shift in the main focus of the public bureaucracy an substance, arguing that it reduces the portion of the government's role that the single agent shifts to citizens in the position of sovereign owners and is always encouraged to participate in the implementation of development and public services. Maining approach of public is not the state but the putting citizen. Democratization is an analysis of the modern bureaucratic theory of classical bureaucratic forms that prioritize the role and function of government structures in governance of productivity-based and professional organizations. The perspective of the administration of public becomes the administration of public or administration by public which becomes the key issue of bureaucracy in the service barometer. Inherent with the public service, that public policy is one of the crucial domains in it. Good policy, Good Public Policy will realize quality public service. Regional Regulation (Perda) of Pamekasan Regency Number6 Year 2010About Retribution of Parking Service at Public Road and Levy of Special Parking Area in Pamekasan Regency is one of the articulation form of more concrete governmental interest in the form of regional regulation in principle to maximize the role of government as a public servant that is giving optimal service to the community, providing legal certainty about parking management, giving parking regulators certainty.